Pulsed Radiofrequency Combined With Methylene Blue Paravertebral Nerve Block Effectively Treats Thoracic Postherpetic Neuralgia - Ji, Meiduan; Yao, Peng; Han, Zhenkai; Zhu, Danlin (Frontiers in Neurology, 2022)
Objective: To compare the effect, safety and patient satisfaction of pulsed radiofrequency combined with methylene blue paravertebral nerve block and pulsed radiofrequency alone in the treatment of thoracic postherpetic neuralgia (PHN). Methods: Seventy-two patients with PHN diagnosed in the Department of Pain Management of Shengjing Hospital at China Medical University, from September 2019 to April 2021, were enrolled in the study. Patients were randomly divided into two groups. Group A (n = 36) received pulsed radiofrequency treatment. Group B (n = 36) received pulsed radiofrequency + methylene blue paravertebral nerve block. Patients were followed-up at 1 day, 1 week, 1 month, 3 months, and 6 months after treatment. Observation at each follow-up included basic patient characteristics, Visual Analog Scale (VAS), Hospital Anxiety and Depression Scale (HAD), the insomnia severity index (ISI), patient satisfaction, complications, and side effects. Results: Compared with preoperative values, the VAS scores significantly decreased in both groups at each post-operative time point (1 day, 1 week, and 1, 3, and 6 months; all P < 0.05). Compared with group A, VAS scores in group B were significantly lower 1 week and 1 month after surgery (P < 0.05). Patients in group B had lower HAD scores than those in group A 1 week after surgery (P < 0.05). Patients in group B had lower ISI scores than those in group A 1 day, 1 week, and 1, 3, and 6 months after surgery (P < 0.05). The pregabalin dosage in group B was lower than that in group A at 1 and 6 months after surgery (P < 0.05). Patient satisfaction was higher in group B than in group A at 1 week and 6 months after surgery (P < 0.05). There were no serious complications or side effects in either group. Conclusion: Pulsed radiofrequency combined with methylene blue paravertebral nerve block is superior to pulsed radiofrequency alone in the treatment of thoracic PHN, which can significantly relieve PHN and improve the condition of sleep and emotional disorders. Therefore, it is a safe and effective treatment method.